Auxin mediated synthesis of gold nanoparticles: a novel approach to enhance shoot and root growth in pearl millet - Sahil; Chaudhary, Anis Ahmad; Sorout, Sonia; Yadav, Kushi; Ali, Mohamed A. M.; Boufahja, Fehmi; Kumar, Vikram; Jain, Devendra; Verma, Kumar Sambhav (Frontiers in Plant Science, 2025)
IntroductionPearl millet, a staple in arid areas, usually suffers from inadequate root development due to environmental stressors. Specifically, using nanotechnology, gold nanoparticles (AuNPs) provide a revolutionary way to improve plant development.MethodsAuxins, specifically Indole-3-acetic acid (IAA) and Indole-3-butyric acid (IBA), were used as stabilizing and reducing agents in the synthesis of AuNPs. UV-Vis, FTIR, SEM, zeta potential, and DLS studies were used to characterize the nanoparticles. Their effect on pearl millet seedlings was evaluated by in vitro tests.ResultsThe control seedlings had shoot and root lengths of 2 cm and 3.5 cm, respectively. With IAA-AuNPs, shoot and root lengths increased to 5.25 cm and 6.75 cm, while with IBA-AuNPs, they increased to 4.75 cm and 7.75 cm. No phytotoxic effects were discovered.DiscussionPearl millet development was markedly enhanced by IAA- and IBA-stabilized AuNPs, indicating their potential as safe and efficient growth enhancers in situations impacted by stress.